Spookiness, Sea Sponges, Stardust, and the Sacred: The Ethics of Quanto-Bio-Cosmic Ontological Interdependence - Porter, Andrew Stone (Journal of religious ethics, 2021)
Developments in twentieth-century science upended the classical Newtonian paradigm that posited a mechanistic universe of atomized entities, regular forces, and natural laws. Trajectories in quantum, biological and cosmic sciences began to indicate instead a paradigm of entanglement and relativity. Religious ethicists and theologians, especially feminists, have interpreted the new model by adopting “interdependence” as a relational-ontological symbol. What are the implications of this move for religious ethics? I consider a selection of representative works that ascribe normative value to quanto-bio-cosmic ontological interdependence. The contemporary scientific paradigm affirms feminist and liberationist relational ontologies, but the attempt to synthesize an “ethico-onto-epistemology” from natural processes inevitably runs up against the fact/value distinction as well as ethical ambiguities intrinsic to natural interdependence. These issues must be addressed if interdependence is to survive as a theological ethical symbol.